Thematic Mapping: A Tool for Urban Governance. Contributions of Classical Graphic Semiology in the Context of New Geographical Paradigm - Pueyo-Campos, Ángel; Postigo-Vidal, Raúl; Arranz-López, Aldo; Zúñiga-Antón, María; Sebastián-López, María; Alonso-Logroño, María Pilar; López-Escolano, Carlos (Revista de Estudios Andaluces, 2016)
Under the paradigm of neography on the use of mapping tools, this paper presents a reflection and different experiences that combine the classic contributions of cartographic semiotics with the new demands of citizens needs. The exhibition media, web pages or thematic atlas have become the tools to participate and cooperate in the city, interact with experts and citizens, strengthen the capacity of citizens to empower, and to know the reality of scientific objectivity geographical space who live.